Impact of Farmer FIRST Project on Livelihood of Farmers - De, Himansu Kumar; Iyemperumal, Sivaraman; Das, Manoj Kumar; Sahoo, Prabhati Kumari; Das, Pratap Chandra; Sarkar, Subhas; Debbarma, Jackson; Rath, Durga Prasad (Indian Journal of Extension Education, 2021)
Under the farmer FIRST project about 400 beneficiary farmers were provided access to improved agricultural technologies in Khordha district. Skill training and demonstration of modules on improved technologies on Crop, Horticulture, Livestock and Fishery were conducted. Following the DFID framework (1999) the impact on livelihoods of farmers was measured through finding a comparative position of physical, social, financial, human and natural assets of the farmers before and after the adoption of the interventions. A structured interview schedule was developed and data was collected from 87 randomly selected beneficiaries by personal interview method twice (before i.e., in 2016-17 and after the intervention i.e., in 2019-20).Â  The mean value of overall standard of living of adopted farmers derived through the addition of the index values of five assets was worked out to be 2.84 in the post-adoption period against 2.41 in the pre-adoption period. Paired sample t-test indicates the positive and significant impact of the project on the livelihood of the beneficiaries.Â